Possibilité de contrôle automatique de la qualité du liège par vision artificielle - Benkirane, Hatim; Benslimane, Rachid; Hachmi, M'Hamed; Sesbou, Ahmed (Ann. For. Sci., 2001)
The quality control often requires some visual inspection systems for defects detection in industrial production. In such application, those systems offer more reliability and lower processing time than a human operator. So this paper aims to introduce an automatic procedure to quality control of cork bits used for quality estimation of cork stacks, which is based on digital image analysis techniques. This procedure tries to quantify defects density of cork bit and to classify them in different quality classes. Experimental results are presented in order to evaluate the performance of the proposed automatic procedure.
Keywords: Classification; cork quality control; defect quantification; digital image; visual system

Possibilité de contrôle automatique de la qualité du liège par vision artificielle (Ann. For. Sci., 2001)
The quality control often requires some visual inspection systems for defects detection in industrial production. In such application, those systems offer more reliability and lower processing time than a human operator. So this paper aims to introduce an automatic procedure to quality control of cork bits used for quality estimation of cork stacks, which is based on digital image analysis techniques. This procedure tries to quantify defects density of cork bit and to classify them in different quality classes. Experimental results are presented in order to evaluate the performance of the proposed automatic procedure.